Polar coordinate analysis in the study of positional attacks in beach handball. (2nd January 2018) - Navarro, Ana; Morillo, Juan Pablo; Reigal, Rafael E.; Hernández-Mendo, Antonio
Abstract: The aim of this study was to identify the relationships between the various behaviours of the positional attack of beach handball in male and female categories. With a sample of 150 international players (men, n = 90), HOISAN software package was used to analyse 24 observations of matches played at the European Beach Handball Championship. We used observational methodology, specifically a nomothetic/point/multidimensional study design. The data obtained were subjected to a polar coordinate analysis from the perspective of genuine retrospectivity. Seven focal behaviours – related to how the attack ends and the player who finishes it – were chosen. The results revealed differences by gender. In the women's category, positional attacks tended to focus on inflight shots; the plays were elaborate and relied on the player in the role of "specialist" for successful execution. In the men's category, in contrast, attacks tended to end with a spin shot when the observed team was trailing in the score and when the opposing team used an open defence; the men's teams also relied more on the pivot to create open spaces. The differences shown suggest intervening in each category with a specific orientation to lead to improvements in the performance of each of them.